Little fires everywhere : a novel - Ng, Celeste (New York : Penguin Press, 2017)
"In Shaker Heights, a placid, progressive suburb of Cleveland, everything is planned -- from the layout of the winding roads, to the colors of the houses, to the successful lives its residents will go on to lead. And no one embodies this spirit more than Elena Richardson, whose guiding principle is playing by the rules. Enter Mia Warren -- an enigmatic artist and single mother -- who arrives in this idyllic bubble with her teenaged daughter Pearl, and rents a house from the Richardsons. Soon Mia and Pearl become more than tenants: all four Richardson children are drawn to the mother-daughter pair. But Mia carries with her a mysterious past and a disregard for the status quo that threatens to upend this carefully ordered community. When old family friends of the Richardsons attempt to adopt a Chinese-American baby, a custody battle erupts that dramatically divides the town -- and puts Mia and Elena on opposing sides."--Provided by Publisher
The New York Times Best Seller List
Keywords: Single mothers -- Fiction; Motherhood -- Fiction; Female friendship -- Fiction; Adoption -- Fiction; Family secrets -- Fiction; Interracial adoption -- Fiction; Custody of children -- Fiction; Family life -- Fiction; FICTION -- Asian American; FICTION -- Family Life; FICTION -- Literary; Shaker Heights (Ohio) -- Fiction; Domestic fiction; Psychological fiction; Fiction; Domestic fiction